2016
DOI: 10.1186/s12934-016-0598-0
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic poly-3-d-hydroxybutyrate production from xylose in recombinant Saccharomyces cerevisiae using a NADH-dependent acetoacetyl-CoA reductase

Abstract: BackgroundPoly-3-d-hydroxybutyrate (PHB) that is a promising precursor for bioplastic with similar physical properties as polypropylene, is naturally produced by several bacterial species. The bacterial pathway is comprised of the three enzymes β-ketothiolase, acetoacetyl-CoA reductase (AAR) and PHB synthase, which all together convert acetyl-CoA into PHB. Heterologous expression of the pathway genes from Cupriavidus necator has enabled PHB production in the yeast Saccharomyces cerevisiae from glucose as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…Based on the fact that PHB accumulation by H. bluephagenesis TD01 is mainly a fermentation process consuming NADH under oxygen limitation condition, NADH/NAD + ratio becomes very important to channel the acetyl-CoA flux to PHB synthesis (Anderson and Dawes, 1990;de las Heras et al, 2016). The NADH/NAD + ratio varies from species to species, it is usually less than 1, with the only exception of Pseudomonas aeruginosa (Farhana et al, 2010;Wimpenny and Firth, 1972), which contains phenazine as the electron receptor under hypoxic condition, this is similar to the acetoacetyl-CoA reduction during PHB synthesis by H. bluephagenesis TD01 (Farhana et al, 2010).…”
Section: Assays Of Cellular Nadh/nad + Ratios In H Bluephagenesismentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the fact that PHB accumulation by H. bluephagenesis TD01 is mainly a fermentation process consuming NADH under oxygen limitation condition, NADH/NAD + ratio becomes very important to channel the acetyl-CoA flux to PHB synthesis (Anderson and Dawes, 1990;de las Heras et al, 2016). The NADH/NAD + ratio varies from species to species, it is usually less than 1, with the only exception of Pseudomonas aeruginosa (Farhana et al, 2010;Wimpenny and Firth, 1972), which contains phenazine as the electron receptor under hypoxic condition, this is similar to the acetoacetyl-CoA reduction during PHB synthesis by H. bluephagenesis TD01 (Farhana et al, 2010).…”
Section: Assays Of Cellular Nadh/nad + Ratios In H Bluephagenesismentioning
confidence: 99%
“…The limitations on essential nutrients (such as N, P, S, Fe and Mg) and presence of sufficient carbon source are critical for most known NADPH dependent species to accumulate PHA (Steinbüchel, 1991). While oxygen limitation has been proven functional for inducing PHA synthesis only in A. beijerinckii and recombinant Saccharomyces cerevisiae harboring phaCAB genes from A. vinosum, as both contain NADH consumable PhaB (Portugal-Nunes et al, 2017;de las Heras et al, 2016;Jackson and Dawes, 1976;Senior and Dawes, 1971;Senior and Dawes, 1973).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the biosynthesis of PHB, the conversion of acetoacetyl-CoA to 3-hydroxybutyryl-CoA is an important step, which catalyzed by the NADH-dependent 3-hydroxybutyryl-CoA dehydrogenase (encoding by hcd) or the NAD(P)H-dependent acetoacetyl-CoA reductase (encoding by phaB) (Figure 5a). The NAD(P)H pool and the ratio of NAD(P)H/NAD(P) + could signi cantly in uence the content of PHB [40,41]. The sequence alignment showed that there is a copy of hcd gene in the genome of S. hygroscopicus var.…”
Section: The In Uence Of Cofactor Concentration On Polyhydroxybutyratmentioning
confidence: 99%